Hepatitis C Virus in Pregnancy: A Systematic Review of the Literature - Andes, Alexandra; Ellenberg, Kerry; Vakos, Amanda; Collins, James; Fryer, Kimberly (American Journal of Perinatology, 2020)
Objective The aim of this study was to systematically review the literature to summarize recent demographic characteristics of hepatitis C virus (HCV) infection during pregnancy and the efficacy of risk-based versus universal screening.Study Design PubMed, EMBASE, and Cochrane Library were searched to identify relevant studies. Studies that recognized hepatitis C as a primary or secondary outcome, with pregnant women as the population and written in English, were included. Studies were excluded if they were abstracts only, written in foreign language, or published prior to 1992. Two researchers independently screened all the studies by titles, abstracts, and full text. Conflicts were settled by a third researcher.Results A total of 698 studies were identified with 78 fitting inclusion criteria. In total, 69 epidemiologic and 9 comparison studies were found. Identified risk factors for HCV infection include intravenous or illicit drug use, sexually transmitted coinfection, high-risk behaviors in the partners, high parity, and history of miscarriages or abortions. Demographic characteristics associated with HCV include non-Hispanic white race, American Indian or Alaskan Native ethnicity, and increasing age. Providers may fail to adequately screen for each risk factor, and up to two-thirds of women with a known risk factor are not screened under current guidelines. Finally, up to 27% of HCV+ women have no identifiable risk factors for infection.Conclusion There is evidence that risk-based screening fails to identify a large proportion of HCV positive women in pregnancy and that pregnant women with HCV risk factors and consistent with current screening guidelines fail to be tested. We urge for the adoption of universal screening to identify these women and offer treatment.
Keywords: hepatitis C virus; pregnancy; screening; prenatal care